The Use of Virtual Measuring Toolkit toward Students' Cognitive and Procedural Knowledge Achievements - Adam, A S; Lutfiyah, A; Mubarok, H; Suprapto, N (Journal of physics. Conference series, 2020)
Virtual laboratory known as VMT (Virtual Measuring Toolkit) has been developed to succeed in the learning objection in a Junior High School level. This VMT was used in measurement on a natural science subject to involve the active participation in measuring process in an unavailable real laboratory facility. This media contains various measurement tool (caliper, three-arm balance, stopwatch, measuring glass for volume and grid for the area) to use for measuring process with the real using approach. Besides, VMT applies in a complete instruction process, integrate to worksheet and assessment sheet. Furthermore, this particular study aimed to measure the students' cognitive and procedural knowledge achievement with the support of VMT and describe its attainment level on that knowledge based on certain criteria. The variables measured in an examination setting on 49 students. Besides, the students' responds to relating media uses are discussed. As a result, the students' achievement on cognitive and procedural knowledge after the Virtual Measuring Toolkit (VMT) using in learning setting on classroom state in a good with percentage of 69 %. While the students' positive responds percentage on 85 %.